Admissions to the National Forensic Mental Health Service Anteceding and Succeeding Its Relocation: A Dundrum Forensic Redevelopment Evaluation Study (D-FOREST) - Muhammad Umer Iqbal; M. Umer Waqar; Harry G Kennedy; Mary Davoren (BJPsych Open, 2024)
Aims The Central Mental Hospital is the Republic of Ireland's only secure forensic hospital and the seat of its National Forensic Mental Health Service (NFMHS). We scrutinised admission patterns in the NFMHS during the period 01/01/2018–01/10/2023; before and after relocating from the historic 1850 site in Dundrum to a modern facility in Portrane on 13/11/2022.